Application and Kinematics Analysis of Noncircular Gear Swinging Guide Bar mechanism - Cai Jun (Jixie chuandong)
In order to satisfy the specific engineering application requirements of swinging guide bar mechanism,the swing guide bar mechanism can be driven by motor output one-way variable motion under the conditions of each bar length is determined,the output motion characteristic of the swing guide bar mechanism is optimized and the comprehensive performance is improved.Considering the non-circular gear transmission characteristic,by using uniform motor driven non-circular gear for one-way variable motion function,which can also achieve the same movement request.The movement diversity and applicationof the mechanism is verified,at the same time,a reliable research method of the series assembly mechanism,reverse design of non-circular gear and optimization design is provided.